High‐Performance and Low‐Temperature Lithium–Sulfur Batteries: Synergism of Thermodynamic and Kinetic Regulation. Issue 18 (15th March 2018) - Fan, Chao‐Ying; Zheng, Yan‐Ping; Zhang, Xiao‐Hua; Shi, Yan‐Hong; Liu, Si‐Yu; Wang, Han‐Chi; Wu, Xing‐Long; Sun, Hai‐Zhu; Zhang, Jing‐Ping
Abstract: The intrinsic polysulfides shuttle, resulting from not only concentration‐gradient diffusion but also slow conversion kinetics of polysulfides, bears the primary responsibility for the poor capacity and cycle stability of lithium–sulfur batteries (LSBs). Here, it is first presented that enriched edge sites derived from vertical standing and ultrathin 2D layered metal selenides (2DLMS) can simultaneously achieve the thermodynamic and kinetic regulation for polysulfides diffusion, which is systematically elucidated through theoretical calculation, electrochemical characterization, and spectroscopic/microscopic analysis. When employed to fabricate compact coating layer of separator, an ultrahigh capacity of 1338.7 mA h g −1 is delivered after 100 cycles at 0.2 C, which is the best among the reports. Over 1000 cycles, the cell still maintains the capacity of 546.8 mA h g −1 at 0.5 C. Moreover, the cell exhibits outstanding capacities of 1106.2 and 865.7 mA h g −1 after 100 cycles at stern temperature of 0 and −25 °C. The superior low‐temperature performance is appealing for extended practical application of LSBs. Especially, in view of the economy, the 2DLMS is recycled as an anode of lithium‐ion and sodium‐ion batteries after finishing the test of LSBs. The low‐cost and scalable 2DLMS with enriched egde sites open a new avenue for the perfect regulation of the sulfur electrode. Abstract : The enriched edge sites derived from vertical mono‐ or few‐layer 2D layered metal selenides achieve preferential chemical adsorption of polysulfides. Concurrently, polysulfides conversion is promoted via the electron transfer between edge sites and adsorbed polysulfides. When employed for separator modification, polysulfides are well stabilized on the cathode region, which endows lithium–sulfur batteries with the best cycle stability and low‐temperature performance.